Proposta de uma oficina para a prática docente no ensino fundamental: utilizando o Cabri na investigação de quadriláteros - Costa, Adilson Oliveira da (2008)
The objective of this study is to suggest a workshop about learning practice to basic education teachers using the dynamic Geometry provided by Cabri Géomètre software. The main investigation was: how would Dynamic Geometry create a learning atmosphere for the study of notable quadrilateral? The hypothesis was that the development of the activities with the help of a computer as a learning instrument and the use of the chosen program would bring a contribution to a review or even to the acquisition of new subject through the built figurers exploration, supposition survey and by the interaction of the group. The workshop was proposed with the expectation that teachers would be more secure when they approach subjects related to the quadrilateral proprieties and also to give them instruments to improve their formation. Using a research-project also named teaching experimentation as research methodology, it was organized a workshop to teachers (research-phase 1) as source of observation to each activity developed. After analysis, considerations and corrections, at the end of this study it is proposed a new version of this workshop to be used to others interested teachers (research- phase 2). The activities were studied according to the comprehension levels from Van Hiele (1957). The conclusion for this first phase was that Dynamic Geometry promoted the creation of a learning atmosphere once it allows a different way of work; teachers noticed the proprieties of notable quadrilateral, this observation would be more difficult in a traditional way (paper and pencil). Others fundamental aspects of the workshop were the experience exchange among the participants and the interaction of all involved, essentials aspects for a teaching experiment